Pesticide poisoning in Zhejiang Province, China: a retrospective analysis from 2008 to 2022 - Fang Wei; Panqi Xue; Xinglin Fang; Xiaoming Lou; Jingyi Sun; Hua Zou; Lifang Zhou (BMC Public Health)
Abstract Background Pesticide poisoning has emerged as a significant public health concern on a global scale. China has a diverse range of agricultural practices and varying pesticide usage across its regions. Nevertheless, there is a paucity of research on the epidemiology of pesticide poisoning in China. To address this research gap, our study was undertaken to investigate the epidemiological characteristics of pesticide poisoning in Zhejiang Province. Methods Pesticide poisoning data for Zhejiang Province from 2008 to 2022 was extracted from the National Occupational Disease and Occupational Health Information Monitoring System. A descriptive statistical analysis had been employed to explore the temporal, demographic, and regional distribution of pesticide poisoning cases. Furthermore, logistic regression models were conducted to analyze the influence factors of pesticide-related death. Results Between the years 2008 and 2022, totally 64,605 pesticide poisoning cases were observed in Zhejiang Province, with a case fatality rate of 5.28%. The incidence rate was estimated as 7.23 per 100,000 population. The poisoning cases number, incidence rates and the case fatality rates all exhibited fluctuating decreasing trends during the study period. Intentional poisoning (suicide) accounted for 64.64% of all poisoning cases, and the case fatality rate of intentional poisoning cases were also significantly higher than occupational and accidental poisoning. In examining the influence factors of pesticide-related death, it was revealed that older individuals, males, and those experiencing either accidental or intentional poisoning had higher risk of death. The analysis also identified that patients treated in township level hospitals exhibited a higher risk of death compared with those in district/county level or provincial/municipal level primary care hospitals. Conclusions The current situation of pesticide poisoning in Zhejiang Province remains severe and the government should further strengthen the monitoring and governing of pesticide. Moreover, it is imperative that mental health education and early psycho-social interventions be given greater emphasis to effectively reduce pesticide-related suicides.